Author |
Topic: Binomial theorem (Read 1660 times) |
|
Steve_B.
Newbie
![*](http://www.ocf.berkeley.edu/~wwu/YaBBImages/star.gif)
![](http://www.ocf.berkeley.edu/~wwu/YaBBImages/avatars/blank.gif)
Posts: 1
|
![](http://www.ocf.berkeley.edu/~wwu/YaBBImages/xx.gif) |
Binomial theorem
« on: Jan 16th, 2012, 3:35pm » |
Quote Modify
|
Binomial theorem to complex numbers; (a + i*b)^n (i*b)^1 = i*b, (i*b)^3 = -i*b^3, (i*b)^5 = i*b^5, (i*b)^7 = -i*b^7, (i*b)^9 = i*b^9, (i*b)^11 = -i*b^11, (i*b)^13 = i*b^13, (i*b)^15 = -i*b^15, (i*b)^17 = i*b^17, (i*b)^19 = -i*b^19,... So, we get a negative sign for n of the form 4*n + 3 For even numbers of n: (i*b)^2 = -b^2, (i*b)^4 = b^4, (i*b)^6 = -b^6, (i*b)^8 = b^8 The signs alternate, we get a negative sign before a real number for numbers congruent to 2 mod 4: a(n) = 4n+2, and a positive sign for multiples of 4. (a + i*b)^n = a^n + C(1,n) a^(n-1) (i*b) + C(2,n) a^(a-n) * (-b^2) + C(3,n) a^(n-3) * (-b^3) + C(4,n) a^(n-4) * (b^4) + ... + (i*b)^n how can the last term be expressed? Is z^n = (a + i*b)^n of the form x^2 + i * y^2 ?
|
|
IP Logged |
|
|
|
|